5-HT(4)-elicited positive inotropic response is mediated by cAMP and regulated by PDE3 in failing rat and human cardiac ventricles - Afzal, F (Nature Publishing Group, 2008)
BACKGROUND AND PURPOSE: The left ventricle in failing hearts becomes sensitive to 5-HT parallelled by appearance of functional G(s)-coupled 5-HT(4) receptors. Here, we have explored the regulatory functions of phosphodiesterases in the 5-HT(4) receptor-mediated functional effects in ventricular muscle from failing rat and human heart. EXPERIMENTAL APPROACH: Extensive myocardial infarctions were induced by coronary artery ligation in Wistar rats. Contractility was measured in left ventricular papillary muscles of rat, 6 weeks after surgery and in left ventricular trabeculae from explanted human hearts. cAMP was quantified by RIA. KEY RESULTS: In papillary muscles from postinfarction rat hearts, 5-HT(4) stimulation exerted positive inotropic and lusitropic effects and increased cAMP. The inotropic effect was increased by non-selective PDE inhibition (IBMX, 10 μM) and selective inhibition of PDE3 (cilostamide, 1 μM), but not of PDE2 (EHNA, 10 μM) or PDE4 (rolipram, 10 μM). Combined PDE3 and PDE4 inhibition enhanced inotropic responses beyond the effect of PDE3 inhibition alone, increased the sensitivity to 5-HT, and also revealed an inotropic response in control (sham-operated) rat ventricle. Lusitropic effects were increased only during combined PDE inhibition. In failing human ventricle, the 5-HT(4) receptor-mediated positive inotropic response was regulated by PDEs in a manner similar to that in postinfarction rat hearts. CONCLUSIONS AND IMPLICATIONS: 5-HT(4) receptor-mediated positive inotropic responses in failing rat ventricle were cAMP-dependent. PDE3 was the main PDE regulating this response and involvement of PDE4 was disclosed by concomitant inhibition of PDE3 in both postinfarction rat and failing human hearts. 5-HT, PDE3 and PDE4 may have pathophysiological functions in heart failure.